Alternative method of helium liquification achieved by analyzing the correlation of critical exponent β and the magnetocaloric parameters. (December 2021) - Mondal, Binita; Dan, Shovan; Mondal, Sudipta; Ranganathan, R.; Mazumdar, Chandan
Abstract: This report deals with the finding of unusually large adiabatic temperature change ( Δ T a d ) parameter related to the magnetocaloric properties of the intermetallic compound ErIr 3 . The maximum isothermal magnetic entropy change ( | Δ S M | ) and maximum adiabatic temperature change ( Δ T a d ) are 12 J.kg -1 K -1 and 14.9 K, respectively, at a field change of 0 → 70 kOe near 5.5 K. Additionally, the system does not exhibit any thermal and field hysterias loss. The high values of the said parameters (in the vicinity of helium liquification temperature) indicate that ErIr 3 can be used as a greener alternative to compressor-based He liquification technology. During analysing the origin of such high values of magnetocaloric parameters, we found a mathematical correlation between the magnetocaloric parameters and the critical exponents of the phase transition. The proposed correlation may narrow the focus of the researchers engaged in searching a material with a potential to show a good magnetocaloric merit.